2017
DOI: 10.7554/elife.24623
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are necessary for epimorphic regeneration in African spiny mice

Abstract: How the immune system affects tissue regeneration is not well understood. In this study, we used an emerging mammalian model of epimorphic regeneration, the African spiny mouse, to examine cell-based inflammation and tested the hypothesis that macrophages are necessary for regeneration. By directly comparing inflammatory cell activation in a 4 mm ear injury during regeneration (Acomys cahirinus) and scarring (Mus musculus), we found that both species exhibited an acute inflammatory response, with scarring char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
162
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(182 citation statements)
references
References 124 publications
(182 reference statements)
9
162
3
Order By: Relevance
“…While macrophages are present in similar numbers to CD‐1 in the underlying fascia and at the wound margins, the A. cahirinus dermis displays very little to no staining of F4/80, Iba‐1 and cd206 positive macrophages up until about day 7 or 10 after wounding . This is similar to the observation by Simkin et al . that the blastema of regenerating ear holes in A. cahirinus is nearly devoid of classically activated macrophages.…”
Section: Skin Regeneration After Full‐thickness Excision or Burn Injurysupporting
confidence: 85%
“…While macrophages are present in similar numbers to CD‐1 in the underlying fascia and at the wound margins, the A. cahirinus dermis displays very little to no staining of F4/80, Iba‐1 and cd206 positive macrophages up until about day 7 or 10 after wounding . This is similar to the observation by Simkin et al . that the blastema of regenerating ear holes in A. cahirinus is nearly devoid of classically activated macrophages.…”
Section: Skin Regeneration After Full‐thickness Excision or Burn Injurysupporting
confidence: 85%
“…Here, macrophages were identified and genetic mapping studies revealed that specific alleles of the natural resistance-macrophage protein 1( NRAMP 1), a divalent metal transporter in macrophages, was shown to interact with inflammatory alleles to affect healing (42). In a recent study using the related rodent strain African spiny mouse , depletion of macrophages led to reduced ear hole closure (43,44) supporting a positive macrophage role in the regenerative response.…”
Section: The Role Of Inflammation and The Innate Immune Responsementioning
confidence: 91%
“…These results suggest a central role for macrophages in limb regeneration by resolving inflammation by shifting cytokine ratios in favor of the anti‐inflammatory subset, and by ECM degradation, including the basement membrane. Macrophages are also necessary for the regeneration of ear punch hole tissue in the African spiny mouse Acomys , which occurs by the formation of a blastema around the rim of the wound (Simkin, Gawriluk, Gensel, & Seifert, 2017). Pro‐inflammatory macrophages fail to penetrate the blastema tissue, but clodronate treatment eliminating both pro‐ and anti‐inflammatory macrophages results in scarring.…”
Section: Formation Of the Accumulation Blastemamentioning
confidence: 99%